Land Use Changes due to Urban and Agricultural Expansion in the Llaucano Basin, Cajamarca (1995- 2024) - Gastolomendo Malimba, Edilberto; Barboza Estela, Willy Overly; Rojas Gonzales, Verónica Judith; Licapa Redolfo, Gladys Sandi (LACCEI, 2025)
Abstract – This study analyzes land use changes in the Llaucano Basin, Hualgayoc Province, Cajamarca, between 1995 and 2024, using Landsat satellite imagery and the Corine Land Cover methodology. The results reveal significant transformations, particularly an increase in artificialized areas, which rose from 3.39% to 11.84%, driven by urban expansion, infrastructure development, and mining activities. Simultaneously, agricultural areas decreased from 15.73% to 11.73%, while natural pastures increased their coverage, reflecting a shift toward livestock activities at the expense of intensive agriculture. Water surfaces and shrubland categories experienced significant reductions, while burned areas expanded, highlighting environmental impacts such as habitat fragmentation and the loss of ecosystem services. These trends are influenced by both human activities and climate change, emphasizing the region’s vulnerability. The study underscores the need for sustainable strategies that integrate biodiversity conservation with economic development. It proposes implementing reforestation, sustainable agricultural practices, and proper urban planning to mitigate negative impacts and ensure the long-term sustainability of the basin’s ecosystems. These findings provide key insights for environmental management in similar contexts.